Assigning a structural motif using spontaneous molecular dipole orientation in thin films. Issue 46 (8th November 2018) - Roman, M.; Dunn, A.; Taj, S.; Keolopile, Z. G.; Rosu-Finsen, A.; Gutowski, M.; McCoustra, M. R. S.; Cassidy, A. M.; Field, D.
Abstract : Guided by the spontelectric behaviour of thin films of cis -methyl formate, infrared observations and computational investigations reveal the dimer structural motif of the crystalline solid. Abstract : Spontaneous orientation of molecular dipoles has been observed to produce bulk electric fields, termed 'spontelectric' fields, in a broad variety of molecular solid thin films formed by condensation from the gas phase. Such spontelectric fields are found in cis -methyl formate ( cis -MF) and the present work combines observation of these fields with high quality ab initio studies of cis -MF monomers and dimers. This enables a prediction of the structural motif within the unit cell of the crystalline phase of solid cis -MF, showing it to be a non-polar dimer. Dimer formation at deposition temperatures of >90 K is therefore cited to contribute to the observed collapse of the spontelectric field at these temperatures. This is the first time that such a structural prediction has been made using observations of spontelectric behaviour as a key indicator.